2003
DOI: 10.1007/s00066-003-1006-3
|View full text |Cite
|
Sign up to set email alerts
|

Remote Afterloading for Neutron Brachytherapy Using Californium-252

Abstract: The technologic concept of the present automatic afterloading device for neutron brachytherapy represents a possible option from the range of conceivable design variants, which - while minimizing technologic and economic requirements - provides the operating personnel with optimum protection and work safety, thus extending the applicability of high LET radiation-based treatment methods in clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…The 5-year overall survival rate of cervical cancer patients who received 252 Cf neutron ray radiotherapy was reported to be 76.8% at stage II and 70.9% at stage III [5]. Another study showed that the 10-year survival rate was better in cervical cancer patients treated with 252 Cf neutron rays than in those treated with gamma radiation (69.1% vs. 50.9%, respectively) [6]. However, despite the improved efficacy of 252 Cf neutron rays in the therapy of cervical cancer, tumors recurrence has been reported.…”
Section: Introductionmentioning
confidence: 99%
“…The 5-year overall survival rate of cervical cancer patients who received 252 Cf neutron ray radiotherapy was reported to be 76.8% at stage II and 70.9% at stage III [5]. Another study showed that the 10-year survival rate was better in cervical cancer patients treated with 252 Cf neutron rays than in those treated with gamma radiation (69.1% vs. 50.9%, respectively) [6]. However, despite the improved efficacy of 252 Cf neutron rays in the therapy of cervical cancer, tumors recurrence has been reported.…”
Section: Introductionmentioning
confidence: 99%
“…The present progress in the technology of production of the miniaturized, highly active source of the 252 Cf nuclide [14,23] as well as the progress in the design concept of the remote afterloading system applied to these sources satisfy the preconditions for introducing neutron brachytherapy in clinical practice [31].…”
Section: Discussionmentioning
confidence: 99%